1991
DOI: 10.1161/01.atv.11.4.940
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipoprotein(a) in patients heterozygous for familial hypercholesterolemia, their relatives, and unrelated control populations.

Abstract: Serum lipoprotein(a) (Lp[a]) levels were significantly higher in 89 patients with heterozygous familial hypercholesterolemia (FH) (geometric mean, 22.7 mg/dl) than in 109 normocholesterolemic controls (10.0 mg/dl, p<0.05) and 40 controls (9.1 mg/dl, /?<0.05) with similarly elevated low density lipoprotein cholesterol levels due to other primary hypercholesterolemias. To provide further evidence that the increased serum Lp(a) concentration was due to inheritance of the FH gene, 24 unaffected first-degree relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 35 publications
4
31
1
1
Order By: Relevance
“…Although some in vitro studies support this proposal (11-13), others do not (42)(43)(44). In addition, several studies have reported that individuals with familial hypercholesterolemia, in which there is a genetic absence of functional LDLRs, have increased plasma Lp[a] levels, suggesting a role for the LDLR and the liver in the plasma clearance of Lp[a] (10,14,15 [a] was ‫%9ف‬ less and hepatic uptake was reduced by ‫%02ف‬ during 24 h. On the other hand, for LDL, the FCR was reduced by ‫%05ف‬ and the hepatic uptake was less than half that for wild-type mice. Thus, it is possible that in wild-type mice the LDLR may make a minor contribution to the hepatic uptake of Lp [a] but that its role is much more limited than it is in the uptake of LDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some in vitro studies support this proposal (11-13), others do not (42)(43)(44). In addition, several studies have reported that individuals with familial hypercholesterolemia, in which there is a genetic absence of functional LDLRs, have increased plasma Lp[a] levels, suggesting a role for the LDLR and the liver in the plasma clearance of Lp[a] (10,14,15 [a] was ‫%9ف‬ less and hepatic uptake was reduced by ‫%02ف‬ during 24 h. On the other hand, for LDL, the FCR was reduced by ‫%05ف‬ and the hepatic uptake was less than half that for wild-type mice. Thus, it is possible that in wild-type mice the LDLR may make a minor contribution to the hepatic uptake of Lp [a] but that its role is much more limited than it is in the uptake of LDL.…”
Section: Discussionmentioning
confidence: 99%
“…These include the LDL receptor (LDLR) (10)(11)(12)(13)(14)(15), megalin/gp330 (16), the LDL receptor-related protein (LRP) (17), and the VLDL receptor (18). The latter two receptors can mediate binding to lipoproteins through apoE.…”
Section: Lipoprotein [A] (Lp[a]mentioning
confidence: 99%
“…Some early studies, whether they found a correlation between Lp(a) concentration and CVD (3)(4)(5)(6) or not (8,9,12,13 ), had smaller sample sizes ranging from 24 (3 ) to 98 (13 ) individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Lp(a) levels may distinguish those patients with familial hypercholesterolaemia and clinically overt coronary heart disease from those without the disease [36,40], although it may also be regarded as a part of the clinical syndrome of familial hypercholesterolaemia [41]. Dietary treatments, such as a vegetation diet [42], have failed to lower serum Lp(a) concentrations in non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%